Case report: Late-onset MELAS syndrome with mtDNA 5783G>A mutation diagnosed by urinary sediment genetic testing - Cai, Hao; Li, Li-Min; Zhang, Miao; Zhou, Yuying; Li, Pan (Frontiers in Genetics, 2024)
Background: Patients with mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS) usually present with multisystemic dysfunction with a wide range of clinical manifestations. When the tests for common mitochondrial DNA (mtDNA) point mutations are negative and the mtDNA defects hypothesis remains, urine epithelial cells can be used to screen the mitochondrial genome for unknown mutations to confirm the diagnosis.Case presentation: A 66-year-old Chinese woman presented with symptoms of MELAS and was initially misdiagnosed with acute encephalitis at another institution. Although genetic analysis of blood lymphocyte DNA was negative, brain imaging, including magnetic resonance imaging, magnetic resonance spectroscopy, and clinical and laboratory findings, were all suggestive of MELAS. Finally, the patient was eventually diagnosed with MELAS with the mtDNA 5783G>A mutation in the MT-TC gene with a urinary sediment genetic test.Conclusions: This case report expands the genetic repertoire associated with MELAS syndrome and highlights the importance that full mtDNA sequencing should be warranted beside the analysis of classical variants when a mitochondrial disorder is highly suspected. Furthermore, urine sediment genetic testing has played a crucial role in the diagnosis of MELAS.